Addressing the needs for cultural adaptation of DARE-keepin’ it REAL among Brazilian students: strategies to improve implementation - Juliana Y. Valente; Bianca Franciosi; Rodrigo Garcia-Cerde; Tania Pietrobon; Zila M. Sanchez (Substance Abuse Treatment, Prevention, and Policy)
Abstract Background The widely implemented prevention program in Brazil, PROERD (a translated version of the DARE-kiR program), showed no evidence of effect in preventing drug use in a recent trial. The lack of cultural adaptation and instructors’ deviations from the curriculum were identified as potential reasons for its ineffectiveness. This study aims to identify points of inadequacy of the PROERD program for the Brazilian culture, suggesting strategies for revising the curriculum to improve implementation. Methods We triangulated data obtained from three different groups of study participants: semi-structured interviews with the law enforcement officer who implemented the program, focus groups with students who participated in the program, and questionnaires completed by external experts in the prevention field who evaluated the program’s manuals. Data was analyzed using thematic analysis based on the Ecological Validity Model theory, which encompasses three main axes: methodology, content, and language to identify the main points for cultural adaptation. Results Regarding the program’s methodology, there is an excess of activities with little interactivity involving literacy skills that do not match Brazilian students' cognitive development and require equipment unavailable in Brazilian public schools. Regarding content, activities were considered appropriate for evidence-based prevention; however, there were some contradictions related to the drug content. The language presented in the program’s manuals was considered inappropriate for the culture of Brazilian youth (vocabulary, examples, and images). Conclusions In conclusion, this study strongly recommends revising the PROERD curriculum Caindo na Real, ensuring it will align with the international prevention standards and Brazilian Culture.